Russian Painters at the Academy de la Grande Chaumière, Paris, in the Beginning of the 20th Century - Borovskaya, Elena A.; Drozdova, Maria A. (Actual Problems of Theory and History of Art, 2020)
The article studies the origins of inclusion of the 20th-century Russian art scene into the global artistic process through the analysis of early works of famous Russian artists, such as V. Mukhina, B. Ternovets, I. Shadr, Z. Serebryakova, A. Exter, and others, who in the 1900‒1910s took painting and sculpture classes at the Academy Grande Chaumiere in Paris. At the mentioned time, Paris was the center of new trendsand most progressive methods in art. It attracted many artists from Russia. However, this aspect of Russianart history was merely presented in the relevant literature. The research studies the creative development of the Russian artists during their training in Paris. It also highlights the new aspects of artistic education erasing the boundaries between domestic and foreign art in the beginning of the 20th century and explaining the inclusion of the Russian art scene of that period into the global artistic process.
Keywords: art history; art education; painting and sculpture teaching; Academy de la Grande Chaumière; Russian artists in Paris; Bourdelle; Mukhina; Exter